2015
DOI: 10.1016/j.jiph.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cervical cancer screening adherence in urban areas of Nakhon Ratchasima Province, Thailand

Abstract: Cervical cancer is the most common disease among Thai women. The cervical cancer mortality rate has increased in the previous decade. Therefore, this cross-sectional study was conducted to examine the factors associated with cervical cancer screening adherence. Stratified sampling with the proportional to size method was used to select registered women aged 30-60 years. Of the 700 self-administered questionnaires distributed during July and September of 2012, 675 were returned, resulting in a response rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 16 publications
(16 reference statements)
8
41
3
Order By: Relevance
“…This study showed that women who were single/divorced/widowed 3.414 times more likely utilized cervical cancer screening as compared with married women [AOR:3.414, (95%CI:1.299,8.972)]. This result was supported by the study done in Thailand [27]. The possible explanation for this might be single women are more likely educated since they might be young and divorced women or widowed women are a more likely aged and increasing risk with women's age leads the women to have more interest to visit health facilities.…”
Section: Plos Onesupporting
confidence: 64%
“…This study showed that women who were single/divorced/widowed 3.414 times more likely utilized cervical cancer screening as compared with married women [AOR:3.414, (95%CI:1.299,8.972)]. This result was supported by the study done in Thailand [27]. The possible explanation for this might be single women are more likely educated since they might be young and divorced women or widowed women are a more likely aged and increasing risk with women's age leads the women to have more interest to visit health facilities.…”
Section: Plos Onesupporting
confidence: 64%
“…An analysis of the knowledge and behaviours of women aged 40 and over about breast cancer screening methods according to education level showed that the rates of those who knew and did breast self‐examination were significantly lower in illiterate women at our research. Conversely, another results of a study showed that revealed that occupation, marital status, number of children, sexual activity, health insurance scheme, history of oral contraceptive pill use, perceived barriers, perceived benefits and knowledge about cervical cancer prevention were significantly associated with cervical cancer screening adherence (Visanuyothin, Chompikul, & Mongkolchati, ).…”
Section: Discussionmentioning
confidence: 99%
“…The family antecedent of CC would alarm women and lead them to an early screening. In this study, widowed women were more likely to have good knowledge while authors reported that it is married women who did [9,18].…”
Section: Discussionmentioning
confidence: 77%
“…We notice that there is an improvement of knowledge among the more instructed participants, although it is not significant. Many studies reported that level of education is strongly linked to awareness and knowledge of the disease [9][10][11]18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation